2007
DOI: 10.1111/j.1365-2044.2007.05227.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy as a cause of upper airway obstruction

Abstract: Summary A patient presented to the ear, nose and throat department with inspiratory stridor, dysphagia and a sore throat. Clinical and radiological examination was normal. During induction of anaesthesia for a planned microlaryngoscopy, the patient developed complete upper airway obstruction that was overcome by applying positive pressure via a facepiece until awake. He subsequently developed respiratory failure, requiring mechanical ventilatory support. An elective tracheostomy was inserted for his symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Neuronal degeneration in Onuf's nucleus located in spinal segment S2-S4 causes damage to the sacral spinal cord innervating the bladder and rectal sphincter, which in turn leads to clinical signs of defecatory and urinary dysfunction. Previous studies have shown [20][21][22][23][24] that about 76% of patients who were eventually diagnosed with MSA complained of symptoms of abnormal sacral spinal cord function when presenting to a doctor. ese symptoms primarily consist of constipation, urinary retention, urinary incontinence, impotence, and hypotension associated with postural changes.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal degeneration in Onuf's nucleus located in spinal segment S2-S4 causes damage to the sacral spinal cord innervating the bladder and rectal sphincter, which in turn leads to clinical signs of defecatory and urinary dysfunction. Previous studies have shown [20][21][22][23][24] that about 76% of patients who were eventually diagnosed with MSA complained of symptoms of abnormal sacral spinal cord function when presenting to a doctor. ese symptoms primarily consist of constipation, urinary retention, urinary incontinence, impotence, and hypotension associated with postural changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal anesthesia can also be suitable in such patients [ 13 ]. Dangerous airway obstruction upon induction of or emergence from general anesthesia may occur, but this obstruction is relatively easy to overcome by applying minimal positive pressure [ 14 ]. There were no such complications in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The inferior olives and the dorsal motor nucleus of the vagus and pyramidal tracts are also affected. The smaller diameter fibers of the autonomic nervous system appear to be the first involved, followed by the gamma fibers and alpha fibers [1, 9]. The clinical diagnosis of MSA is difficult and there are no pathognomonic features to discriminate the Parkinsonian variant (MSA-P) from Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, the patient presented clinical and imaging criteria that could establish MSA as possible diagnosis. This procedure was not usual since the main complaints (respiratory insufficiency and vocal cords paralysis) are rare manifestations of MSA and only few articles relating these to MSA can be found in literature [79, 11, 12]. In 2006, Glass et al [12] reported 6 cases of irregularities in respiration that may occasionally arise in an early stage of MSA and may be clues to diagnosis.…”
Section: Discussionmentioning
confidence: 99%